Formation of the Figge Maar Seafloor Crater During the 1964 B1 Blowout in the German North Sea - Jens Karstens; Jens Schneider von Deimling; Christian Berndt; Christoph Böttner; Michel Kühn; Benedict T. I. Reinardy; Axel Ehrhardt; Jonas Gros; Bettina Schramm; Dirk Klaeschen; Judith Elger; Matthias Haeckel; et al. (Earth Science, Systems and Society)
In 1964, exploration drilling in the German Sector of the North Sea hit a gas pocket at ∼2900 m depth below the seafloor and triggered a blowout, which formed a 550 m-wide and up to 38 m deep seafloor crater now known as Figge Maar. Although seafloor craters formed by fluid flow are very common structures, little is known about their formation dynamics. Here, we present 2D reflection seismic, sediment echosounder, and multibeam echosounder data from three geoscientific surveys of the Figge Maar blowout crater, which are used to reconstruct its formation. Reflection seismic data support a scenario in which overpressured gas ascended first through the lower part of the borehole and then migrated along steeply inclined strata and faults towards the seafloor. The focused discharge of gas at the seafloor removed up to 4.8 Mt of sediments in the following weeks of vigorous venting. Eyewitness accounts document that the initial phase of crater formation was characterized by the eruptive expulsion of fluids and sediments cutting deep into the substrate. This was followed by a prolonged phase of sediment fluidization and redistribution widening the crater. After fluid discharge ceased, the Figge Maar acted as a sediment trap reducing the crater depth to ∼12 m relative to the surrounding seafloor in 2018, which corresponds to an average sedimentation rate of ∼22,000 m3/yr between 1995 and 2018. Hydroacoustic and geochemical data indicate that the Figge Maar nowadays emits primarily biogenic methane, predominantly during low tide. The formation of Figge Maar illustrates hazards related to the formation of secondary fluid pathways, which can bypass safety measures at the wellhead and are thus difficult to control.